Adsorption of methylene blue dye by different methods of obtaining shrimp residue chitin - Iliane Muller Otto (Associação Brasileira de Engenharia Sanitária e Ambiental, 2021)
The textile industry, very important for the world economy, generates an effluent containing dyes, and which, when discarded in water bodies without proper treatment, can cause impacts to human health and the environment. One of these widely used dyes is methylene blue, whose characteristics are high solubility in water and its toxic potential, and which effects range from eye irritations, nausea, vomiting and even mental confusion. Among the potential adsorbents of this dye is chitin, which is a biopolymer extracted from the shrimp exoskeleton. Aiming at the development of a low-cost adsorbent material with potential use in the textile effluent treatment industry, the ability to remove methylene blue dye by shrimp residue chitin, obtained by eleven different methodologies, was verified. The three most efficient treatments reached approximately 75% of dye removal, proving the high adsorption power of shrimp residue. In addition to providing technological development of materials, the research brings socioeconomic benefits to the fishermen’s colony with the use of shrimp residue for the adsorption of other waste from the textile industry, contributing to the sustainability of both activities and reducing the environmental impact.